2021
DOI: 10.1108/ijchm-03-2021-0331
|View full text |Cite
|
Sign up to set email alerts
|

From curious to connoisseur: a longitudinal segmentation of attendees at a Chinese wine festival

Abstract: Purpose This study aims to examine the components and evolution of the Chinese wine festival market using the Dalian International Wine and Dine Festival (DIWDF) as a case study. Design/methodology/approach Adopting a longitudinal approach, survey data were collected from attendees of the first, fifth and seventh DIWDF in 2012, 2016 and 2018, respectively. Cluster analysis segmented attendees by wine and festival experience and consumption features. Comparative analysis was conducted to examine segment diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 118 publications
(161 reference statements)
0
8
0
Order By: Relevance
“…Internationally, wine consumers are also becoming younger (García-Cortijo et al , 2019), indicating a trend that transcends national culture. Shi et al (2022) found wine festival goers in the 25–44 age range (that of millennials in the USA at the time of this writing) account for the majority (51.6%) of wine lovers and fest enthusiasts (older generations accounted for 20.2%). The knowledge and comfort level with wine that younger consumers have developed often far exceeds those of older generations.…”
Section: Resultsmentioning
confidence: 77%
“…Internationally, wine consumers are also becoming younger (García-Cortijo et al , 2019), indicating a trend that transcends national culture. Shi et al (2022) found wine festival goers in the 25–44 age range (that of millennials in the USA at the time of this writing) account for the majority (51.6%) of wine lovers and fest enthusiasts (older generations accounted for 20.2%). The knowledge and comfort level with wine that younger consumers have developed often far exceeds those of older generations.…”
Section: Resultsmentioning
confidence: 77%
“…, 2020; Sharma et al. , 2020; Shi et al. , 2022), and the average score of each segment on the different SB is shown in Table 12.…”
Section: Empirical Analysis and Resultsmentioning
confidence: 99%
“…Based on this, further considering the balance of distribution among all the segments, this study finally decided to divide the entire Chinese wine market into three categories, namely (1) the most valuable customers, (2) valuable customers and (3) customers with low contribution. And Table 10 shows the value ranking and distribution of the three markets, Table 11 shows the demographical characteristics of each segment to further observe the differences among the different groups and have a better understanding of the practical meanings of our obtained market segmentation results as in (Goncalves et al, 2020;Sharma et al, 2020;Shi et al, 2022), and the average score of each segment on the different SB is shown in Table 12.…”
Section: Results Of Market Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…This type of segmentation has sometimes been criticised for being more of a sectorisation than a segmentation (Rezaei & Ortt, 2013). For this reason, in recent years there has been a tendency to use relational-type criteria, that is, linked to the behaviours and assessments that companies make of their relationship with their providers (Heirati et al, 2016;Thomas, 2016;Brotspies & Weinstein, 2019;Shi et al, 2022), as well as criteria associated with the use of technologies (Weinstein, 2014;Fuentes et al, 2017).…”
Section: Introductionmentioning
confidence: 99%